2005
DOI: 10.1007/s00335-005-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

A paternally imprinted QTL for mature body mass on mouse Chromosome 8

Abstract: Body mass (BM) is a classic polygenic trait that has been extensively investigated to determine the underlying genetic architecture. Many previous studies looking at the genetic basis of variation in BM in murine animal models by quantitative trait loci (QTL) mapping have used crosses between two inbred lines. As a consequence it has not been possible to explore imprinting effects which have been shown to play an important role in the genetic basis of early growth with persistent effects throughout the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…The ML method cannot identify any significant QTL at the genome level; however, the L 2 E method successfully detects one genome-wide significant QTL at 2 cM to the leftmost proximal marker on the chromosome 8. Coincidently, in 2005, Rance et al [28] reported a significant QTL for the mature mice body mass located at 7 cM to the leftmost proximal marker on the chromosome 8, almost at the same location for the significant QTL identified here. Our finding hence further validates the existence of a significant QTL for mice body mass at the beginning of the chromosome 8.…”
Section: Resultssupporting
confidence: 75%
“…The ML method cannot identify any significant QTL at the genome level; however, the L 2 E method successfully detects one genome-wide significant QTL at 2 cM to the leftmost proximal marker on the chromosome 8. Coincidently, in 2005, Rance et al [28] reported a significant QTL for the mature mice body mass located at 7 cM to the leftmost proximal marker on the chromosome 8, almost at the same location for the significant QTL identified here. Our finding hence further validates the existence of a significant QTL for mice body mass at the beginning of the chromosome 8.…”
Section: Resultssupporting
confidence: 75%
“…Obtaining significant results for body composition traits is consistent with imprinting effects on human adult obesity and body composition (Georges et al, 2003; Gorlova et al, 2003; Dong et al, 2005) and on adult obesity and body composition in mice (Casellas et al, 2009). It is now known that imprinting marks, such as DNA methylation and histone configurations, often persist into adulthood (Gorlova et al, 2003; Christensen et al, 2009; Trowbridge and Orkin, 2010; Woodfine et al, 2011; Wu et al, 2011), and that imprinting may play a physiological role in metabolism and body composition throughout life, thereby contributing both to normal variation and the architecture of complex traits rather than being restricted to prenatal and neonatal effects (Rance et al, 2005; Smith et al, 2006; Cheverud et al, 2008; Casellas et al, 2009; Hager et al, 2009; Garfield et al, 2011). Our current understanding of the function of imprinted genes is overwhelmingly biased toward growth and development (Constancia et al, 2005; Abu-Amero et al, 2006; Delaval et al, 2006; Fowden et al, 2006; Fradin et al, 2006; Smith et al, 2006, 2007; Wu et al, 2006; Jiang et al, 2007; Charalambous et al, 2010) and only recently have we begun to gain a better understanding in mice of the effects of genomic imprinting on physiological traits expressed long after embryogenesis and fetal development (Rance et al, 2005; Cheverud et al, 2008; Casellas et al, 2009; Hager et al, 2009; Garfield et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Imprinted genes also appear to be involved in postnatal energy metabolism as several diseases caused by mutations in imprinted genes lead to obesity (e.g. Prader-Willi syndrome, pseudohypoparathyroidism type 1A) and population studies have identified a number of chromosomal regions associated with parent-of-origin effects on energy balance in humans (Dong et al, 2005; Gorlova et al, 2003; Lindsay et al, 2001; Rance et al, 2005). The effect of GNAS imprinting on energy balance is consistent with the parental conflict hypothesis, a loss of the paternally expressed XLαs leads to a lean phenotype with increased sympathetic nerve activity and energy expenditure while the oppositely imprinted GNAS gene product G s α leads to obesity due to opposite effects on sympathetic nerve activity and energy expenditure.…”
Section: Discussionmentioning
confidence: 99%